The slow demographic transition in regions vulnerable to climate change - Thang Dao; Matthias Kalkuhl; Chrysovalantis Vasilakis (Osaka University, Institute of Social and Economic Research (ISER), 2022)
This paper considers the persistent effects of climate change on the speed of demographic transi- tion, and hence on the size of the population in regions that are the least developed and the most vulnerable to climate change, such as Sub-Saharan Africa. These effects are transmitted through interactions between the education gender gap within families, fertility, and the local environment, through which the demographic transition is delayed. Environmental conditions affect intra-household labor allocation because of the impacts on local resources under the poor infrastructural system. Ex- amples include the collection of essential resources, e.g. clean water and firewood, by women for their families' daily lives. Climate change causes damage to local resources, offsetting (partially) the role of technological progress and infrastructure investment in saving time that women spend on their housework duties. Hence, the gender inequality in education/income is upheld, delaying declines in fertility and creating population momentum. The bigger population, in turn, degrades local resources and the environment through expanded production. The interplay between local resources, gender inequality, and population, under the persistent effect of climate change, may thus generate a slow demographic transition and stagnation of the least developed regions. We provide empirical confir- mation for our theoretical predictions using data from 44 African countries in the period from 1960 to 2017.
Keywords: J11; J16; Q01; Q20; Q54; Q56; 330; Climate change; local resource; fertility; gender inequality in education; slow demographic transition